귤 과피 분말을 첨가한 피막제 처리에 의한 돈육의 저장성 향상 - 최현정; 김용석; Hyeonjeong Choi; Yong-Suk Kim (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2023)
This study aimed to investigate the effect of a coating agent on pork storage. Pork was coated with a coating agent containing sodium carboxymethyl cellulose (CMC) and mandarin peel powder (M). The treatments were divided into control, a 0.1% CMC treatment, and a 0.1% CMC +5% M treatment, and pH, color, 2-thiobarbituric acid reactive substances (TBARS), volatile basic nitrogen (VBN), and the number of viable cell counts were measured. In the case of redness (a), it was found that the reduction over the storage period was less in the 0.1% CMC + 5% M treatment than in the control and the 1% CMC treatment. When stored at 4oC and 25oC, TBARS of pork tended to increase during the storage period, followed by control, 0.1% CMC treatment, and 0.1% CMC + 5% M treatment, indicating that lipid oxidation was most suppressed in pork coated with mandarin peel powder. As a result of measuring the VBN of pork stored at 4oC and 25oC, the 0.1% CMC + 5% M treatment showed lower values than the control and 0.1% CMC treatment. When the film-coated pork was stored at 4oC, the number of viable cell counts in the 0.1% CMC +5% M treatment area was 7.13±0.96 log CFU/g on the 12th day of storage, delaying the growth of viable cell counts for approximately 3 d more than other treatments. Therefore, coating pork with a film containing CMC and mandarin peel powder has been confirmed to delay the increase in the number of viable cell counts while reducing the quality change during pork storage, which is an effective alternative to improving the storage of fresh food as an edible film.